2004
DOI: 10.1021/jm049904b
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Derivatives as Ligands of the Farnesoid X Receptor. Synthesis, Evaluation, and Structure−Activity Relationship of a Series of Body and Side Chain Modified Analogues of Chenodeoxycholic Acid

Abstract: The farnesoid X receptor (FXR) is activated by endogenous bile acids (BAs) and plays a variety of physiological roles related to modulation of gene transcription. In particular, FXR positively regulates the cholesterol catabolism while feedback inhibits the BA synthesis by repressing the expression of the CYP7A and CYP8B genes. We have previously shown that 6alpha-ethyl-CDCA (6ECDCA) is a potent and selective FXR agonist. In this paper we report an extensive structure-activity relationship for a series of synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 41 publications
2
111
0
1
Order By: Relevance
“…Pharmacological activation of FXR was obtained by in vivo and in vitro treatment with 6-ethyl-CDCA (INT-747), a semisynthetic FXR ligand that activates the receptor with an EC 50 of Ϸ 100 nM (21)(22)(23). The efficacy of INT-747 was tested in acute and chronic models of colon inflammation induced by trinitrobenzenesulfonic acid (TNBS) or dextran sulfate (DSS) (24,25).…”
Section: Colitis Induction Study Design and Isolation And Stimulatimentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological activation of FXR was obtained by in vivo and in vitro treatment with 6-ethyl-CDCA (INT-747), a semisynthetic FXR ligand that activates the receptor with an EC 50 of Ϸ 100 nM (21)(22)(23). The efficacy of INT-747 was tested in acute and chronic models of colon inflammation induced by trinitrobenzenesulfonic acid (TNBS) or dextran sulfate (DSS) (24,25).…”
Section: Colitis Induction Study Design and Isolation And Stimulatimentioning
confidence: 99%
“…TNBS colitis was induced by intrarectal administration of TNBS (0.5 mg/mouse) in 50% ethanol (21,22). Mice receiving TNBS were randomized to receive no treatment or INT-747 at a dose of 5 mg/kg (n ϭ 10 for each group).…”
Section: Colitis Induction Study Design and Isolation And Stimulatimentioning
confidence: 99%
“…In addition to their role in bile acid homeostasis, FXRs have been found to regulate liver regeneration during liver injury (33)(34)(35)(36)(37)(38). Obeticholic acid (OCA, INT-747), a 6-ethyl derivative of the natural human bile acid chenodeoxycholic acid (CDCA), is a first-in-class selective FXR agonist with ~ 100-fold greater FXR agonistic activity than CDCA (39)(40)(41). In a male Wistar rat model of cholestasis, OCA protected hepatocytes against deleterious effects caused by administration of lithocholic acid (LCA) (41).…”
Section: Farnesoid X Receptor Agonists and Pscmentioning
confidence: 99%
“…Two major patterns of modification were elaborated around the BA scaffold, namely, those affecting the B ring of the steroid nucleus and those relating to the side chain [15][16][17][18][19][20][21][22][23]. These studies have revealed that even minor modifications designed to obtain a desired biological activity, can also significantly affect the physico-chemical properties, metabolic behaviour, distribution within different districts and tissues, and, most importantly, the cytotoxicity profile of the new analogues with respect to the parent natural BA [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations and following our interest in BA research [15,16,[18][19][20][21][22], in this paper, we investigate the effect of BA side chain modifications with respect to their capacity to generate micelles. In particular, we report the synthesis, CMC evaluation and structure-property considerations of a series of hyodeoxycholic acid (HDCA) derivatives characterized by a different side chain length and by the presence of a methyl group at the alpha position of the carboxylic acid tail (Figure 1).…”
Section: Introductionmentioning
confidence: 99%